2021
DOI: 10.3390/molecules26164771
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Study of Bridging N-Donor Ligand-Induced Supramolecular Assembly of Conjugated Zn-Trisporphyrin with a Triphenylamine Core

Abstract: This article studies the supramolecular assembly behavior of a Zn-trisporphyrin conjugate containing a triphenylamine core (1) with bridging N-donor ligands using the UV-vis spectrophotometric titration method at micromolar concentrations. Our results show that pyridine, a non-bridging ligand, formed a 3:1 open complex with 1. The corresponding binding constant was estimated to be (2.7 ± 0.15) × 1014 M−3. In contrast, bridging ligands, 4,4-bipyridine (BIPY) and 1,3-di(4-pyridyl)propane (DPYP), formed stable 3:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In this context, supramolecular assemblies constructed by the directional coordination between porphyrin building blocks and metal complexes are very attractive for the fabrication of nanostructured porphyrin materials. Metal-coordinated directional bonding has successfully provided various multiporphyrin architectures, such as rectangles, 21 squares, 22 ladders, 23 cube cages, 24 double-deckers, 25 and wheel type nano-rings. 26…”
Section: Introductionmentioning
confidence: 99%
“…In this context, supramolecular assemblies constructed by the directional coordination between porphyrin building blocks and metal complexes are very attractive for the fabrication of nanostructured porphyrin materials. Metal-coordinated directional bonding has successfully provided various multiporphyrin architectures, such as rectangles, 21 squares, 22 ladders, 23 cube cages, 24 double-deckers, 25 and wheel type nano-rings. 26…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Porphyrins are the most interesting building block units to form supramolecular assemblies. 21,22 Porphyrin-based porous materials have been studied extensively because of their wide applications in gas storage and separation, 23 biomedical applications, 24 chemical sensors, 25 photoelectric polymers, 26 and heterogeneous catalysis. 27 For example, Ohmura et al demonstrated that a 2-D porphyrin-based MOF from Cu( ii ) naphthoate paddlewheel clusters and Cu( ii ) tetrapyridylporphyrins exhibit selective CO 2 /N 2 separation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these materials have high surface areas, excellent corrosion resistance, high electrical conductivity, outstanding optoelectronic properties, and high thermal stability compared to their parent constituents. Thus, a large number of building blocks have been used to construct nano- and microstructured nanomaterials having well-defined shapes and dimensions. Porphyrinoids (free porphyrin or metalloporphyrin compounds) are emerging building blocks for the fabrication of self-assembled functional nanomaterials having light-harvesting properties or charge-transfer functionality. In general, free porphyrin or metalloporphyrin compounds self-assemble and form large aggregates in solution. Several intermolecular noncovalent interactions (for example, hydrogen bonding, van der Waals, π–π stacking, ligand coordination, electrostatic, hydrophobic, and hydrophilic interactions) are responsible for the self-assembly of porphyrinoid compounds. The morphology of these nanostructures is not always regular, making them unsuitable for practical applications.…”
Section: Introductionmentioning
confidence: 99%